A Design of Variable-configuration Hexapod Robots - Wang Xiaolei; Guo Jikang (Jixie chuandong)
Aiming at the detection task of the complex terrain in the field, a variable-configuration hexapod robot was proposed. The robot can switch between crawling and rolling modes through the change of the leg shape, and it has both fast passing ability and good environmental adaptability. The former leg was taken as the research object for the kinematic analysis, and the formula for the positive and negative solution of its position and the Jacobian matrix were derived. Subsequently, the foot end workspace was solved with the use of the Monte Carlo method. In order to comprehensively evaluate the performance of the robot, the working space, mechanism dexterity and mechanism stiffness were taken as the performance indicators, and they were analyzed afterwards. Furthermore, a multi-objective optimization design model was proposed. According to this model, the scale comprehensive optimization was carried out, and then the optimal structural scale parameters were obtained. The results show that after the optimization, the working space of the front leg is increased by 1.28%, the global dexterity of the front leg is increased by 22.50%, and the stiffness is increased by 42.80%. Finally, according to the optimization results, a prototype was made, which lays a foundation for its subsequent research.